2011
DOI: 10.1111/j.1462-2920.2011.02451.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of sulfate‐reducing bacteria to an artificial oil‐spill in a coastal marine sediment

Abstract: In situ mesocosm experiments using a calcareous sand flat from a coastal area of the island of Mallorca in the Mediterranean Sea were performed in order to study the response of sulfate-reducing bacteria (SRB) to controlled crude oil contamination, or heavy contamination with naphthalene. Changes in the microbial community caused by the contamination were monitored by a combination of comparative sequence analysis of 16S rRNA genes, fluorescence in situ hybridization, cultivation approaches and metabolic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…The highest counts of aromatic-oxidizing bacteria were obtained under sulfate-reducing conditions with benzene, toluene, or naphthalene as a carbon source (see Table S3 in the supplemental material). The microbial diversity and potential for sulfate reduction-dependent hydrocarbon degradation in the sediments where M samples were collected was verified previously (43). As observed for the Atlantic Islands samples, Gammaand Deltaproteobacteria were the most abundant communities in these sediments.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The highest counts of aromatic-oxidizing bacteria were obtained under sulfate-reducing conditions with benzene, toluene, or naphthalene as a carbon source (see Table S3 in the supplemental material). The microbial diversity and potential for sulfate reduction-dependent hydrocarbon degradation in the sediments where M samples were collected was verified previously (43). As observed for the Atlantic Islands samples, Gammaand Deltaproteobacteria were the most abundant communities in these sediments.…”
Section: Resultsmentioning
confidence: 59%
“…Naphthalene was provided by inserting a perforated 10-ml propylene pipette filled with naphthalene crystals into the originally collected core; four lanes of 1-mm holes were distributed equidistantly along the pipette to allow for diffusion. Prestige crude oil was introduced into another core after impregnation onto a nylon stick, as described previously (43). A third core remained untreated and served as a control (M-CON).…”
Section: Methodsmentioning
confidence: 99%
“…The microbial community at these sites changed over time with an increase in potentially hydrocarbon-degrading SRP phylotypes affiliating, e.g., with the Desulfococcus-Desulfonema-Desulfosarcina-like group (Miralles, Grossi, et al, 2007;Miralles, Nérini, et al, 2007). Artificial vertical contamination of sandy sediments in the Mediterranean Alcúdia Bay (Mallorca Island) with oil or naphthalene resulted in a shift of the SRP community structure (Suárez-Suárez et al, 2011). Coastal sediments at the Atlantic Cíes Island (Spain), affected by the Prestige oil spill in late 2002, harboured 1.5-4.8 years after the accident high numbers of Desulfobacteraceae and Desulfarculales members in the oil-polluted anoxic zones (AcostaGonzález, Rosselló-Mora, & Marqués, 2013a).…”
Section: Marine/estuarine Systemsmentioning
confidence: 98%
“…Various studies have demonstrated the capacity of functional gene arrays to detect microbial community responses to environmental stressors Liu et al, 2010;Wang et al, 2009;Ward et al, 2007;Wu et al, 2008;Yergeau et al, 2007;Zhou, 2003), including heavily contaminated habitats (Lu et al, 2012;Neufeld et al, 2006;Van Nostrand et al, 2009;Xie et al, 2011). The results of these studies and other approaches evaluating the response of bacterial communities on environmental perturbation (chemically or physically) have demonstrated changes in the respective community structure and function (dos Santos et al, 2011;Findlay et al, 1990;Suarez-Suarez et al, 2011), thereby forming the basis for our hypothesis.…”
Section: Introductionmentioning
confidence: 76%